Pengaruh Ampas dan Arang Tempurung Kelapa (Cocos Nucifera L) Pada Pertumbuhan Tanaman Mentimun (Cucumis Sativus L) (Sebagai Penunjang Pratikum Materi Pertumbuhan dan Perkembangan Tumbuhan) - Indri Septiana; Herliani Herliani (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
The potential of organic waste such as coconut husk and coconut shell charcoal as a source of organic fertilizer that can enhance plant growth and yield. With the aim of examining the effects of coconut husk and coconut shell charcoal (Cocos nucifera L) on the growth and yield of cucumber plants (Cucumis sativus L), this research utilized an experimental method by applying different doses of coconut husk and coconut shell charcoal to the cucumber plants. The results of the study indicate that the treatment with 200 grams of coconut husk and 200 grams of coconut shell charcoal (treatment A2) had the most significant impact on the growth of cucumber plants, showing a significant increase in the number of leaves, number of fruits, fruit length, and wet fruit weight compared to other treatments. The implications of this research are that the application of coconut husk and coconut shell charcoal can be an environmentally friendly alternative to enhance agricultural productivity, improve soil fertility, and serve as a basis for the development of more sustainable agricultural practices in the future.